A rare case report of spontaneous frothy secretion from intact skin: Role of fungal allergic disease (Indian Journal of Case Reports, 2019)
Fungi are common aeroallergens which form a major part of bioaerosol. About 2-6% of the general population is allergic to fungi belonging to genera Aspergillus, Penicillium, Alternaria and Fusarium in developed countries. Here, we report a case series of 8 school going children of age 8 to 9 years who simultaneously reported with chief complaints of spontaneous mysterious white frothy secretion oozing from the surface of the intact skin while they were attending their classes. The role of fungal allergic reaction was suspected and skin secretions were sent for fungal as well as bacterial culture. Fungal culture done on air sampling plates was found positive for Aspergillus species. Cutaneous manifestations in the form of urticaria, angioedema have been reported in the previous literature, this case report shows a rare phenomenon of spontaneous oozing frothy white secretion which has not been reported in the literature so far.